Rehabilitation outcomes after comprehensive post-acute inpatient rehabilitation following moderate to severe acquired brain injury—study protocol for an overall prognosis study based on routinely collected health data - Uwe M. Pommerich; Peter W. Stubbs; Jørgen Feldbæk Nielsen (Diagnostic and Prognostic Research)
Abstract Background The initial theme of the PROGRESS framework for prognosis research is termed overall prognosis research. Its aim is to describe the most likely course of health conditions in the context of current care. These average group-level prognoses may be used to inform patients, health policies, trial designs, or further prognosis research. Acquired brain injury, such as stroke, traumatic brain injury or encephalopathy, is a major cause of disability and functional limitations, worldwide. Rehabilitation aims to maximize independent functioning and meaningful participation in society post-injury. While some observational studies can allow for an inference of the overall prognosis of the level of independent functioning, the context for the provision of rehabilitation is rarely described. The aim of this protocol is to provide a detailed account of the clinical context to aid the interpretation of our upcoming overall prognosis study. Methods The study will occur at a Danish post-acute inpatient rehabilitation facility providing specialised inpatient rehabilitation for individuals with moderate to severe acquired brain injury. Routinely collected electronic health data will be extracted from the healthcare provider’s database and deterministically linked on an individual level to construct the study cohort. The study period spans from March 2011 to December 2022. Four outcomes will measure the level of functioning. Rehabilitation needs will also be described. Outcomes and rehabilitation needs will be described for the entire cohort, across rehabilitation complexity levels and stratified for relevant demographic and clinical parameters. Descriptive statistics will be used to estimate average prognoses for the level of functioning at discharge from post-acute rehabilitation. The patterns of missing data will be investigated. Discussion This protocol is intended to provide transparency in our upcoming study based on routinely collected clinical data. It will aid in the interpretation of the overall prognosis estimates within the context of our current clinical practice and the assessment of potential sources of bias independently.